Beyond the spectrum integrating neuro-inclusive design to a holistic facility empowering individuals with Autism - Mendoza, Czarina Elaine B. (College of Architecture, University of the Philippines Diliman, 2025)
Addressing the gaps in autism care in the Philippines, particularly for older age groups, this comprehensive design project presents the design of a holistic healthcare facility for individuals with autism, focusing on creating a built environment that empowers them and supports their families. It integrates therapeutic services, vocational training, and transient housing, all within a framework of neuro-inclusive design. Grounded in phenomenological research and interviews, the study identifies the spatial, sensory, and functional needs of individuals with autism. These insights are translated and developed into an architectural design incorporating sensory zoning, intuitive spatial organization, and nature-oriented principles, fostering an environment that promotes well-being and independence. The inclusion of transient homes expanded the typology of the healthcare facility, providing short and long-term accommodations for families traveling from remote areas and transitional spaces for individuals preparing for independent living. Strategically located in Quezon City, the facility's design considers urban accessibility while ensuring a calming, nature-integrated environment within the city's dense context. This project redefines conventional healthcare typologies to create a neuro-inclusive model in the Philippines that empowers individuals with autism and their families through adaptable, safe, and supportive environments.